A Multi-Tenancy Database Approach to Effective Emergency Preparedness and Mitigation - Henry, Ogbu Nwani (IJRDO -Journal of Computer Science Engineering, 2016)
Emergency managements’ sole idea is to reduce occurrences, reduce the intensity of occurrencesor to safeguard lives and properties during emergency situations. Preparedness, Mitigation,Response and Recovery phases are four phases of emergency management. While Mitigationphase is concerned with actions taken to reduce the chances of an accident occurring through riskassessment or early attempts to make the consequences of an accident as small as possible,preparedness phase deals with every method applied to get ready for future imaginable incidents.They include developing systems, managing resources, developing scenarios and plans andengaging in realistic training. Emergency management agencies are in constant search of ways toenhance preparedness and mitigation phases to reduce the chances of accidents occurring. In thisresearch, we present an architecture based on multi-tenancy which consolidates multiple databasesfrom multiple emergency management agencies to improve access to emergency information,strategic planning and risk assessment thereby enabling easy development of emergencymanagement systems (EMS), reducing cost of such development and also its operations.